In the Serious Light of Nothing/#/In the Serious Light of Nothing [[no pinyin available]]. - Dao, Bei (Xianggang guo ji shi ge zhi ye 2013., 2013)
Drawn from International Poetry Nights in Hong Kong 2013, In the Serious Light of Nothing is a chapbook of poetry by Peter Minter presented in English, and Chinese. In the Serious Light of Nothing is also available, along with the chapbooks of other internationally renowned poets, in Islands or Continents (Eighteen-Volume Box Set). Selected poems from this volume are featured in the anthology Islands or Continents: International Poetry Nights in Hong Kong 2013.